Discordant age and sex-specific trends in the incidence of a first coronary heart disease event in Western Australia from 1996 to 2007. Issue 5 (6th January 2011) - Briffa, Tom; Nedkoff, Lee; Peeters, Anna; Tonkin, Andrew; Hung, Joseph; Ridout, Stephen C; Knuiman, Matthew
Abstract : Objective: To determine age- and sex-specific population trends in fatal and non-fatal first coronary heart disease (CHD) events in Western Australia from 1996 to 2007. Design: Longitudinal retrospective population study. Setting: State-wide population. Patients: All residents aged 35–84 years during 1996–2007 who died or were hospitalised with a principal diagnosis of acute CHD. Data sources: Person-linked file of mortality and morbidity records. Main outcome measures: Age-standardised (35–84 years) and age-specific (35–54, 55–69, 70–84 years) rates by gender for a first CHD event were calculated with a 10-year lead-in period to define first events. Results: From 1996 to 2007 there were 36 631 first CHD events, including 8518 (23%) fatal cases in those aged 35–84 years. Overall, age-adjusted rates for fatal first CHD declined 5.3%/year in men (95% CI −6.1% to −4.6%) and 6.5%/year in women (95% CI −7.5% to −5.5%). However, age-specific fatal first CHD rates were neutral in both men aged 35–54 years (0.1%/year; 95% CI −1.8% to 2.1%) and women of the same age, (−1.6%/year; 95% CI −5.6% to 2.5%). Age-specific trends in non-fatal CHD rates reflected the same trends in fatal CHD events in men and women, with rates reportedly increasing in women aged 35–54 years (2.5%/year (95% CI 1.1% to 3.9%). Conclusion: The age-specific decline in fatal and non-fatal first CHD rates in older men and women was not observed in those aged 35–54 years. These novel findings provide evidence for a levelling in the CHD incidence rates in younger adults and puts renewed importance on primary prevention in this group.